Critical issues of converged communication service commercial deployment - Lihua WU; Lei SHEN (Dianxin kexue)
Converged communication service is an important method for telecom operators to compete with OTT （over the top）internet application service.The critical issues of converged communication service commercial deployment were studied.The relation of converged communication service with traditional services was analyzed.The solutions of network deployment were discussed,and the problems of service opening and billing that should be taken into account were proposed.